Effects of Aerobic Plus Resistance Exercise on Body Composition Related Variables in Pediatric Obesity: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Garcia-Hermoso, A (Human Kinetics Publishers Inc., 2015)
The purpose of this meta-analysis of randomized trials was to determine the effectiveness of aerobic plus resistance exercise interventions on body composition related to variables in overweight and obese youth. A computerized search was made of 7 databases. The analysis was restricted to randomized controlled trials that examined the effect of aerobic and resistance exercise on body composition (body weight, body mass index, fat mass, fat-free mass, and waist circumference) in obese youth. Two independent reviewers screened studies and extracted data. Weighted mean differences (WMD) and 95% confidence intervals were calculated. Nine studies were selected for meta-analysis as they fulfilled the inclusion criteria (n = 365). Aerobic plus resistance exercise interventions (8-24 weeks duration) produced a decrease in body weight (WMD=-3.31 kg), body mass index (WMD=-1.05 kg/m2), and fat mass (WMD=-1.93% and 5.05 kg), but changes in fatfree mass and waist circumference were not observed. These changes were accentuated through programs of at least 60 min of exercise per session, generating greater reductions in body weight (WMD=-4.11 kg), fat mass (WMD=-4.07%), and increase in fat-free mass (WMD = 2.45 kg). This meta-analysis provides insight into the effectiveness of short-term aerobic plus resistance exercise interventions for decreasing body weight, body mass index, and fat mass in pediatric obesity. © 2015 Human Kinetics, Inc.